2021
DOI: 10.1108/jfra-11-2020-0324
|View full text |Cite
|
Sign up to set email alerts
|

The short- and long-lived effects of IFRS mandate on IPO firms in emerging market economies

Abstract: Purpose This study aims to examine the short- and long-lived effects of the International Financial Reporting Standards (IFRS) mandate on the quality of reporting information of initial public offering (IPO) firms in emerging market economies. Design/methodology/approach The study used several difference-in-differences models for a sample comprising 102 Saudi Arabian IPO firms for 2003–2017. Findings It found that mandating the application of the IFRS had a significant short-lived but no long-lived effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 83 publications
4
24
0
Order By: Relevance
“…The regression results indicate that the day 1 returns are negatively and significantly related to Ind-AS implying decrease in underpricing with adoption of Ind-AS in the Indian Equity Market. These results align with the work of a few researchers 5,24,26 . However, for the 7th day and 30 th day MAER the relationship is negative but not significant.…”
Section: Multivariate Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The regression results indicate that the day 1 returns are negatively and significantly related to Ind-AS implying decrease in underpricing with adoption of Ind-AS in the Indian Equity Market. These results align with the work of a few researchers 5,24,26 . However, for the 7th day and 30 th day MAER the relationship is negative but not significant.…”
Section: Multivariate Analysissupporting
confidence: 92%
“…However, since the PD required improved and harmonised disclosures in the prospectus, there was a substantial reduction in underpricing in countries where accounting compliance and enforcement had also increased. Jamaani and Alidarous 24 reported that mandating the adoption of IFRS impacts the information asymmetry of IPO firms and thus reduces the levels of underpricing. Tsai and Huang 13 suggested that the adoption of convergent-IFRS in China had mitigated the phenomenon of underpricing which was not moderated by the proportion of ownership by State Owned Enterprises (SOE).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers agree that IFRS requirements lower information asymmetries between market precipitants and improve the quality of financial reporting, resulting in a more transparent market environment (Daske et al, 2008;Hearn, 2014;Houqe and Monem, 2016;Guermazi and Halioui, 2020;Jamaani and Alidarous, 2021;Tsai and Huang, 2021). This is due to IFRS's ability to exclude accounting alternatives, impose additional disclosure IFRS mandatory adoption obligations on users, and define more precise measurement standards than the national Generally Accepted Accounting Principles (GAAPs).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have attempted to understand underpricing in the global IPO market, particularly in developing economies, by examining a range of IPO underpricing determinants (Ekkayokkaya and Pengniti, 2012;Alanazi and Al-Zoubi, 2015;Chen et al, 2017;Ahmad-Zaluki and Badru, 2020;Lee et al, 2020;Jamaani and Ahmed, 2021;Jamaani and Alidarous, 2021)…”
Section: Factors Affecting Initial Public Offering Underpricing In De...mentioning
confidence: 99%
See 1 more Smart Citation